An overview of the development challenges and constraints of the Niger Basin and possible intervention strategies - Namara, Regassa E.; Barry, Boubacar; Owusu, Eric S.; Ogilvie, A. (International Water Management Institute, 2011)
The Niger River Basin covers 7.5% of the African continent and is shared between nine riparian countries. The human population of the basin is growing at an average annual rate of about 3%, which makes the Niger River Basin one of the areas with the highest fertility rates in the world. The desert margin is expanding; climate change is negatively impacting rainfall; and urbanization, industrialization, and the human and livestock population are threatening the quantity and quality of available water resources. The basin population already suffers from chronic poverty. Based on a literature review, this paper suggests some key water-related and other interventions that are capable of easing the basin's development challenges.